2010
DOI: 10.1007/s00405-010-1373-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical measurement to sphenoid sinus for the Chinese in Asia based on CT using sagittal reconstruction images

Abstract: The objective this study was to measure the changes of sphenoid sinusin the Chinese in AsiausingCT sagittal thin-slice reconstruction images, and to clarify the three-dimensional anatomical features of sphenoid sinus with its surrounding structures, relevant to the performing of the endoscopic sphenoidotomy. The sagittal reconstruction images were obtained from 178 CT images of 89 cases of normal adult participants (54 males and 35 females) with sphenoid sinus. We took the high-resolution axial CT images, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 10 publications
(9 reference statements)
2
29
1
2
Order By: Relevance
“…If the surgeon proceeds to more than the defined height, the skull base might be perforated. In a similar study performed by Wu et al [6] on a Chinese population, the average length of Line 1 was found to be 10.6±1.5 mm, demonstrating that in different populations, Line 1 can vary; thus, the surgeon should be aware of these distances when performing endoscopic procedures.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…If the surgeon proceeds to more than the defined height, the skull base might be perforated. In a similar study performed by Wu et al [6] on a Chinese population, the average length of Line 1 was found to be 10.6±1.5 mm, demonstrating that in different populations, Line 1 can vary; thus, the surgeon should be aware of these distances when performing endoscopic procedures.…”
Section: Discussionmentioning
confidence: 64%
“…The mean age was 43.42±14 years Table 1). Onodi cells at the lateral ethmoid sinus were present on the right side in 67 (22%) patients and on the left side in 66 (22%) patients [6]. Onodi cells were present bilaterally in 31 (17 female, 14 male) patients.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations